2018
DOI: 10.1016/j.ijid.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mycobacterium tuberculosis in urine by Xpert MTB/RIF Ultra: A useful adjunctive diagnostic tool in HIV-associated tuberculosis

Abstract: HighlightsUltra has detected Mycobacterium tuberculosis in the urine of a patient with renal TB.Use of Xpert or Ultra on urine is not currently recommended due to lack of evidence.Urine Ultra may be useful in the diagnosis of extra-pulmonary TB in persons with HIV.Further study is required to characterise the diagnostic accuracy of urine Ultra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 12 publications
0
19
0
1
Order By: Relevance
“…According to the published study results, Xpert Ultra was better for TB detection capabilities and it has been demonstrated to have high sensitivities for the rapid diagnosis of pulmonary tuberculosis in children, smear-negative EPTB, tuberculous meningitis in HIV-infected adults, patients with paucibacillary disease and HIV (Bahr et al, 2018;Bisognin et al, 2018;Dorman et al, 2018;Nicol et al, 2018;Perez-Risco et al, 2018). Also, Xpert Ultra was performed on urine to identify disseminated TB in an HIV-infected woman in Uganda (Atherton et al, 2018). However, so far only a few reports have shown the diagnostic performance of Xpert Ultra for EPTB especially in China.…”
Section: Discussionmentioning
confidence: 99%
“…According to the published study results, Xpert Ultra was better for TB detection capabilities and it has been demonstrated to have high sensitivities for the rapid diagnosis of pulmonary tuberculosis in children, smear-negative EPTB, tuberculous meningitis in HIV-infected adults, patients with paucibacillary disease and HIV (Bahr et al, 2018;Bisognin et al, 2018;Dorman et al, 2018;Nicol et al, 2018;Perez-Risco et al, 2018). Also, Xpert Ultra was performed on urine to identify disseminated TB in an HIV-infected woman in Uganda (Atherton et al, 2018). However, so far only a few reports have shown the diagnostic performance of Xpert Ultra for EPTB especially in China.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies examined Ultra on urine specimens ( 28 30 ) and none in patients investigated for TBL. Urine Ultra may obviate invasive sampling (and hence referral to a specialized facility and associated costs and delays).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies examined Ultra on urine [28][29][30] and none in patients investigated for TBL. Urine 275 Ultra may obviate the need for invasive sampling (and hence referral to a specialised facility, 276 and associated costs and delays).…”
Section: Discussion 230mentioning
confidence: 99%